2020
DOI: 10.3892/etm.2020.9084
|View full text |Cite
|
Sign up to set email alerts
|

CLDN3 expression and function in pregnancy‑induced hypertension

Abstract: This aim of the present study was to investigate the expression and function of claudin 3 (CLDN3) in pregnancy-induced hypertension. The mRNA expression levels of CLDN3 in the placental tissue and peripheral blood of patients with pregnancy-induced hypertension were measured using reverse transcription-quantitative PCR. Human trophoblast HTR8/SVneo cells overexpressing CLDN3 were generated using a lentiviral vector. Cell Counting kit-8 (CCK-8) assay, flow cytometry, Transwell chamber assays, confocal laser sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…The cell columns of the guinea pig subplacenta contain the progenitor trophoblast that become invasive trophoblast responsible for maternal vascular remodeling (Verkeste, Slangen et al, 1998). Under MNR conditions we demonstrated reduced Cldn5 expression, unsurprisingly since this has been shown to be down in cases of hypertension and preeclampia (Zhao, Qi et al, 2020;Adu-Gyamfi, Czika et al, 2021). Increased Ocln and Zo1 expression in the sub-placenta/decidua were seen suggesting strong cell adhesion and tight junctions which would not be conducive to EMT for proper invasion.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The cell columns of the guinea pig subplacenta contain the progenitor trophoblast that become invasive trophoblast responsible for maternal vascular remodeling (Verkeste, Slangen et al, 1998). Under MNR conditions we demonstrated reduced Cldn5 expression, unsurprisingly since this has been shown to be down in cases of hypertension and preeclampia (Zhao, Qi et al, 2020;Adu-Gyamfi, Czika et al, 2021). Increased Ocln and Zo1 expression in the sub-placenta/decidua were seen suggesting strong cell adhesion and tight junctions which would not be conducive to EMT for proper invasion.…”
Section: Discussionmentioning
confidence: 78%
“…Through activation of the ERK1/2 pathway, claudin proteins upregulate matrix-metalloproteinases to help break down the extracellular matrix (ECM) as they invade into the maternal tissue and control permeability. mRNA levels of these claudin proteins have also been shown to be down in cases of hypertension and/or preeclampsia, suggesting a role in placental dysfunction ( Zhao, Qi et al, 2020 ). During normal placenta development ZO-1 and occludin are expressed in the proliferating trophoblasts and down regulation of these proteins is associated with the epithelial cell transformation that is necessary for proper invasion of EVTs ( Marzioni, Banita et al, 2001 ).…”
Section: Introductionmentioning
confidence: 99%
“…We then confirmed that CAM expression is required for the invasion of JAR cells, which is in accordance with previous reports noting that CDH4, CLDN3, and ITGAM are involved in the regulation of cell invasion. For example, Schumann et al reported that CLND3 was highly expressed in murine trophoblast giant cells and in human EVT cells and that it plays a role in the regulation of trophoblast invasion (Schumann et al., 2015; Zhao et al., 2020). Similarly, CDH4 deficiency impacts the invasion of human osteosarcoma cells (Tang et al., 2018), and epithelial ovarian cancer (EOC) invasion is mediated by ITGAM (Lyu et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…5 Thereby, PIH is considered one of the main causes underlying the death of pregnant women, and searching for novel strategies for the prevention of PIH would significantly benefit maternal and neonatal outcome. 3 Although the etiology and pathophysiological mechanism of PIH have been gradually unveiled, the specific molecular mechanisms involved in PIH remain incompletely understood. 7,8 Several studies have suggested that the genetic risk factors involved in the renin-angiotensin system (RAS), endothelin system, inflammatory factors, and oxidative stress, are closely associated with PIH.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, fetuses of these PIH mothers are at higher risk of intrauterine growth retardation, prematurity, and intrauterine death 5 . Thereby, PIH is considered one of the main causes underlying the death of pregnant women, and searching for novel strategies for the prevention of PIH would significantly benefit maternal and neonatal outcome 3 . Although the etiology and pathophysiological mechanism of PIH have been gradually unveiled, the specific molecular mechanisms involved in PIH remain incompletely understood 7,8 .…”
Section: Introductionmentioning
confidence: 99%